1975
DOI: 10.1192/bjp.126.5.462
|View full text |Cite
|
Sign up to set email alerts
|

Accidents and Drug Treatment in a Psychiatric Hospital

Abstract: A survey of 351 accidents occurring in a two-year period in a psychiatric hospital showed that 77 per cent of the accidents involved female patients and 48 per cent involved patients with organic psychoses; 236 accidents were falls and 280 occurred in the ward setting. In 277 instances adequate controls were available. Seventy-five per cent of the accident patients had received a psychotropic drug on the day of the accident as opposed to 61 per cent of the controls. The possibility that the side-effects of psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Two studies reported that fallers received psychotropic medication within 24 hours before the fall but did not differentiate between acute changes in medication or chronically administered medication. 15 , 25 Chan et al 21 reported that changes to medication within 24 hours were associated with falling but did not specify which kind of medication. Vaughn et al 19 reported that involuntary hospitalized patients fell more than voluntary patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported that fallers received psychotropic medication within 24 hours before the fall but did not differentiate between acute changes in medication or chronically administered medication. 15 , 25 Chan et al 21 reported that changes to medication within 24 hours were associated with falling but did not specify which kind of medication. Vaughn et al 19 reported that involuntary hospitalized patients fell more than voluntary patients.…”
Section: Resultsmentioning
confidence: 99%
“…Extrinsic risk factors concern medication and environmental factors like clothing, place, time of day, walking aids, and nearby staff. Studies reporting on medication found general psychotropic medication to be associated with falling 9,12,15,16,21 with some studies specifically reporting mood stabilizers, 10,16,21,23 lithium, 19,23 and benzodiazepines 16,22,23 as a risk factor. Specific somatic medication was reported as well, like laxatives, 16 antihypertensives, [21][22][23]25 and alpha blockers.…”
Section: Extrinsic Risk Factorsmentioning
confidence: 99%
“…Our results confirmed it is possible to predict inpatient falls using text analysis of nursing records in a hospital EMR system, with an AUC of 0.834 across an average of five independent experiments. In many previous studies, the prediction of falls was based on specified risk factors, such as the use of psychotropic drugs [28][29][30][31][32], mental state (eg, disorientation, confusion, and delirium) [4,5,30,[33][34][35], impaired motor function (eg, unstable gait and muscle weakness) [4,5,29,32,35], and excretory condition (eg, incontinence and frequent toileting) [5,33,35]. Additionally, the usefulness of nursing records for inpatient fall prediction was discussed recently [36], and it was shown that nursing records contained words known as risk factors for inpatient falls and interventions used in daily practice using NLP analysis.…”
Section: Principal Resultsmentioning
confidence: 99%
“…Other categories showed no difference. It is thought that this finding is of great importance, because although other researchers have indicated a relationship between drugs and nosokomial accidents (Ballinger & Ramsay 1975, McLennan 1976, Ray et al 1989 Creason 1989) they have not identified which drugs contribute to falling.…”
Section: Drugsmentioning
confidence: 89%